MVC Model, Struts Framework and File upload Issues in Web Applications Based on J2EE Platform - Wojciechowski, Jarosław; Sakowicz, Bartosz; Dura, K.; Napieralski, Andrzej (My University, 2004)
This paper describes the web application based on the J2EE platform indicating the MVC model, Struts framework and file upload issues. The development of internet technology and the will to standardize the mechanisms used in implementation of internet applications was the basis background for the development of J2EE platform. The project of International Office TUL internet service is an application based on the above mentioned environment. The specification of the project is closely connected with the activities and needs of the staff of the International Office. The article presents the use of MVC model on J2EE platform on an example of open source Apache/Tomcat application server and the database management system MySql.
Keywords: MVC; Struts; J2EE; JSP; servlet; file upload; JavaBeans; Tomcat